Inflammatory Bowel Disease–Associated Changes in the Gut: Focus on Kazan Patients. Issue 3 (7th August 2020) - Lo Sasso, Giuseppe; Khachatryan, Lusine; Kondylis, Athanasios; Battey, James N D; Sierro, Nicolas; Danilova, Natalia A; Grigoryeva, Tatiana V; Markelova, Maria I; Khusnutdinova, Dilyara R; Laikov, Alexander V; Salafutdinov, Ilnur I; Romanova, Yulia D; et al.
Abstract: Background: Several studies have highlighted the role of host–microbiome interactions in the pathogenesis of inflammatory bowel disease (IBD), resulting in an increasing amount of data mainly focusing on Western patients. Because of the increasing prevalence of IBD in newly industrialized countries such as those in Asia, the Middle East, and South America, there is mounting interest in elucidating the gut microbiota of these populations. We present a comprehensive analysis of several IBD-related biomarkers and gut microbiota profiles and functions of a unique population of patients with IBD and healthy patients from Kazan (Republic of Tatarstan, Russia). Methods: Blood and fecal IBD biomarkers, serum cytokines, and fecal short-chain fatty acid (SCFA) content were profiled. Finally, fecal microbiota composition was analyzed by 16S and whole-genome shotgun sequencing. Results: Fecal microbiota whole-genome sequencing confirmed the presence of classic IBD dysbiotic features at the phylum level, with increased abundance of Proteobacteria, Actinobacteria, and Fusobacteria and decreased abundance of Firmicutes, Bacteroidetes, and Verrucomicrobia. At the genus level, the abundance of both fermentative (SCFA-producing and hydrogen (H2 )-releasing) and hydrogenotrophic (H2 -consuming) microbes was affected in patients with IBD. This imbalance was confirmed by the decreased abundance of SCFA species in the feces of patients with IBD and the change in anaerobic index, which mirrors the redox status of the intestine. Conclusions: Our analyses highlighted how IBD-related dysbiotic microbiota—which are generally mainly linked to SCFA imbalance—may affect other important metabolic pathways, such as H2 metabolism, that are critical for host physiology and disease development.